2017
DOI: 10.1177/1557085117738326
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Justice With Female Offenders: The Neglected Role of Gender in Restorative Conferencing

Abstract: This article presents findings from a new qualitative study into female offenders' experiences of restorative conferencing in England and Wales. It is argued that gendered factors of crime and victimization have a definite impact on the restorative conference process, particularly in the areas of complex and interacting needs, differently natured conference engagements, and risks around shame, mental health, and stereotypical ideals of female behavior. For women to reap the full benefits of restorative justice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
(66 reference statements)
1
27
2
Order By: Relevance
“…Processes of cumulative disadvantage can snare individuals into persistent offending via decreasing life chances limiting their opportunities for action (Sampson & Laub, 1997). It has been recognized that women suffer harder from labeling due to their double deviance, as women offenders both break the rule of law and defy gender norms proclaiming women to be respectable and morally exemplary (Lander, 2015; Österman & Masson, 2018; Skeggs, 1997). To be labeled as deviant is to be excluded from society, which is why desistance from crime necessitates a processual re-approximation and reintegration into the mainstream (Braithwaite, 1989; Maruna, LeBel, Mitchell, & Naples, 2004).…”
Section: Future Aspirations Among Desistersmentioning
confidence: 99%
“…Processes of cumulative disadvantage can snare individuals into persistent offending via decreasing life chances limiting their opportunities for action (Sampson & Laub, 1997). It has been recognized that women suffer harder from labeling due to their double deviance, as women offenders both break the rule of law and defy gender norms proclaiming women to be respectable and morally exemplary (Lander, 2015; Österman & Masson, 2018; Skeggs, 1997). To be labeled as deviant is to be excluded from society, which is why desistance from crime necessitates a processual re-approximation and reintegration into the mainstream (Braithwaite, 1989; Maruna, LeBel, Mitchell, & Naples, 2004).…”
Section: Future Aspirations Among Desistersmentioning
confidence: 99%
“…If appropriate support through partnership working has been provided and it is felt that it would be ethical and suitable for a woman to meet her victim, her ability to engage in a restorative intervention may then be determined by how and when the process is introduced. Previously it has been argued by the current authors (Osterman and Masson, in print) that relationship building plays a ‘particularly important role for effective working with female offenders’, and that additional investment from a practitioner is more likely to result in a more positive and effective restorative experience. Communication emerged in the data as playing a significant role in fostering a supportive and trustworthy relationship with female offenders, including, for example, assuring a woman that restorative justice will not involve being cross-examined or interrogated:Personally I think if there’s people that can explain it to them…that they’re not being told off and they’re not being told they have to do it as part of their sentence, it is just something they might want to do…For women, [communication] is needed.…”
Section: Factors To Consider For Effective and Ethical Restorative Prmentioning
confidence: 86%
“…In support of previous research (Miles, 2013), the study found clear evidence of an inconsistent approach to gender-aware practice in the restorative justice field. It has been argued by the current authors in a recent article (Osterman and Masson, in print) that there is demonstrable disagreement regarding practitioners’ roles and responsibilities in the field in relation to gender-specificity in working approaches. However, the findings in this study clearly indicate that gender plays a role in the conference process, and that there are particular factors that need to be considered at each stage of the proceedings in order to allow for the full benefits of restorative justice to be reaped by female offenders.…”
Section: Factors To Consider For Effective and Ethical Restorative Prmentioning
confidence: 95%
“…The last three decades has witnessed significant advancements into understanding the specific needs and problems facing women that often precipitate highly gendered pathways into offending and/or victimisation. Yet as Österman and Masson (2018: 5) note, ‘the currently expanding field of restorative justice has remained firmly outside of these advancements. There is a consequently a “woeful lack of evidence” regarding female offenders’ interactions with, and experiences of, restorative justice conferencing [Miles, 2013: 8]’.…”
Section: State Offences and Systemic Injusticesmentioning
confidence: 99%
“… 3. See recent research from Österman and Masson (2018: 21) on the use of RJ conferencing in England and Wales where they note, ‘restorative justice shares many of the problems faced in wider criminal justice settings, with the legacy of female victimization experiences presenting a huge concern in contemporary penalty’. …”
mentioning
confidence: 99%